2021
DOI: 10.1051/e3sconf/202131403002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of climate change on water inflow of the three largest dams in the Beni Mellal-Khenifra region

Abstract: Drought and water scarcity are resulting from the effects of climate change during recent decades. The region of Beni Mellal Khenifra, by the nature of its economic activities based particularly on agriculture and the availability of water resources, is considered among the most vulnerable regions to the effects of climate change in Morocco. In this paper, we analyzed the impact of climate change on the three largest dams in the region (Hassan first, Bin El Ouidane and Ahmed El Hansali), based on statistical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The region of Beni-Mellal Khenifra is characterized by a semi-arid climate and by a very high agricultural vulnerability due to the climate variability. In our previous studies, we have demonstrated that the temperature are unstable and trend to increase in different areas of the region including Tadla plaine (EL Baki et al, 2021).…”
Section: Evolution Of Climate Parametersmentioning
confidence: 96%
“…The region of Beni-Mellal Khenifra is characterized by a semi-arid climate and by a very high agricultural vulnerability due to the climate variability. In our previous studies, we have demonstrated that the temperature are unstable and trend to increase in different areas of the region including Tadla plaine (EL Baki et al, 2021).…”
Section: Evolution Of Climate Parametersmentioning
confidence: 96%